Synthesized methodological approaches for estimation of fruit production of wild edible species. - Hounkpevi, Achille; Gandji, Kisito; SALAKO, Kolawolé Valère; ASSOGBADJO, ACHILLE EPHREM (Assogbadjo A.E., Okou F.A.Y. & Sinsin B., 2020)
There are several evidences of the prominent roles that non-timber forest products (NTFPs), and particularly wild edible fruit (WEF) play for human food security and poverty alleviation. Although neglected in the past, there are increasing interest on WEF species, and evaluation of their fruit production has become essential. Quantifying the fruit production of WEF species is important to assess their contribution to food security and poverty alleviation but also to plan their sustainable exploitation. In the last three decades, several studies have investigated the productivity of some WEF species. However, the methodological approaches are diverse and there is a need to provide guidelines particularly for early researchers interested by this research field. This chapter provides a methodological synthesis to serve as guidelines for students and researchers for a better assessment of the fruit production of WEF species. The chapter focuses on techniques for sampling, data collection and data analysis. Overall, three main aspects are often investigated across studies. These include (i) potential in fruit production, (ii) effects of abiotic factors such as soil, and climate on fruit production, (iii) relationships between morphological parameters of trees (e.g. diameter and height) and fruit production. Three main methodological approaches are used by researchers: the integral counting of fruits, the collection and counting of fruits fallen under the tree, and the estimation by extrapolation. Each of these approaches was presented and illustrated through a case study.